KEMAMPUAN FERMENTASI BAL DENGAN SUBSTRAT SUSU KACANG MERAH - Hastuti, Luthfiana Indah; Retnaningrum, Endah (Universitas Muhammadiyah Surakarta, 2020)
The oligosaccharide content in red beans can be broken down with groups of microorganisms, namely lactic acid bacteria. This decomposition is done by the fermentation process. Lactic acid bacteria used in this study were Lactococcus lactis subsp. lactis NBRC 12007. This study aims to determine BAL Lactococcus lactis subsp. Lactis NBRC 12007 in the fermentation process of red bean juice and regulates the difference in quality by fermentation of UHT cow's milk with the same starter bacteria. Beginner Lactococcus lactis subsp. lactis NBRC 12007 was added 3% to the substrate of red bean extract and UHT cow's milk. Fermentation is carried out for 24 hours at 37oC. The results showed that the total cell, total acid, total protein, pH, antibacterial and physical values were much better and improved the quality of the fermented red bean extract substrate product compared to the fermentation with UHT cow's milk substrate.